Prevalence and Factors Associated with Motorcycle Road Traffic Accidents among Undergraduate Students at a Higher Education Institution in Trang Province, Thailand - Sangsiri, Pornkanokwan; Mudchiew, Thanarat; baka, Maimunni; Narkrod, Chompunut; kamlangkuea, Wilaiwan; Phasuk, Supawadee (Disease Control Journal, 2025)
This cross-sectional descriptive study aimed to examine the prevalence and factors associated with motorcycle accidents among undergraduate students in a higher education institution in Trang Province. The study included 299 participants. Data were collected in January 2025 using an online questionnaire distributed through Google Forms. The questionnaire covered personal factors, motorcycle information, riding environment, knowledge, attitudes, and behaviors related to accident prevention, as well as data on motorcycle accidents. Descriptive statistics and binary logistic regression analysis were applied at a significance level of 0.05. The results showed that 22.41% (95% CI=17.70-27.10) of the participants had experienced at least one motorcycle-related accident. The highest occurrence of accidents was observed in the evening (4 p.m.-6 p.m.). Environmental factors, such as rainfall and slippery road conditions, played a significant role in causing accidents. Factors significantly associated with motorcycle accidents among the participants included gender (COR=2.50, 95% CI=1.23-5.10), age (COR=1.96, 95% CI=1.13-3.40), and the experience of family members who had previously been involved in motorcycle accidents (COR=3.15, 95% CI=1.72-5.79). Male students, those aged over 20, and those with a family history of motorcycle accidents were more likely to experience accidents than other groups. Based on these findings, it is recommended to develop programs that promote safe driving among youth, enhance the enforcement of helmet use regulations, and provide training on driving in adverse weather conditions. These measures aim to enhance safety and sustainably reduce motorcycle accidents among students.